2001
DOI: 10.1074/jbc.m104080200
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptotic Regulatory Protein ARC (Apoptosis Repressor with Caspase Recruitment Domain) Prevents Oxidant Stress-mediated Cell Death by Preserving Mitochondrial Function

Abstract: ARC is an apoptotic regulatory protein expressed almost exclusively in myogenic cells. It contains a caspase recruitment domain (CARD) through which it has been shown to block the activation of some initiator caspases. Because ARC also blocks caspase-independent events associated with apoptosis, such as hypoxia-induced cytochrome c release, we examined its role in cell death triggered by exposure to hydrogen peroxide (H 2 O 2 ) in the myogenic cell line, H9c2. Cell death in this model was caspase-independent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
92
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 37 publications
9
92
1
2
Order By: Relevance
“…It can interact with Fas, FADD and Bax, 33,38 inhibit cytochrome c release 39 and maintain mitochondrial membrane potential. 40,41 These lines of evidence suggest that ARC is a critical factor for maintaining the cellular function. Our present work reveals that ARC participates in the regulation of autophagy to maintain the equilibrium between autophagic cell death and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…It can interact with Fas, FADD and Bax, 33,38 inhibit cytochrome c release 39 and maintain mitochondrial membrane potential. 40,41 These lines of evidence suggest that ARC is a critical factor for maintaining the cellular function. Our present work reveals that ARC participates in the regulation of autophagy to maintain the equilibrium between autophagic cell death and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, anemia has been associated with higher mortality in cardiac patients and, by stimulating hematopoiesis, EPO may increase O 2 delivery to the myocardium, resulting in some functional benefit (24,29). On the other hand, correction of hematocrit may not translate into therapeutic gains.…”
Section: Discussionmentioning
confidence: 99%
“…ARC transgenic mice exhibit less myocardial infarction sizes (56), whereas ARC knock-out mice demonstrate accelerated myocardial infarction (47). ARC levels are significantly decreased in cardiomyocytes upon treatment with hydrogen peroxide and hypoxia (20,23). Furthermore, ARC levels are reduced upon heart failure (47) or ischemia (57).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed that ARC also may elicit its anti-apoptotic function by other means. It can interact with Fas, FADD, and Bax (20,21), inhibit cytochrome c release (22), and maintain mitochondrial membrane potential (23,24). Despite ARC's abundant expression and blocking apoptosis induced by either intrinsic or extrinsic stimulus, cardiomyocytes still undergo apoptosis under pathological conditions such as oxidative stress (23,25) and hypoxia (26 -28).…”
mentioning
confidence: 99%